Demulsification of W/O emulsion at petroleum field and reservoir conditions using some demulsifiers based on polyethylene and propylene oxides - A.M. Alsabagh; M.E. Hassan; S.E.M. Desouky; N.M. Nasser; E.A. Elsharaky; M.M. Abdelhamid (Egyptian Journal of Petroleum)
In this work, polymer molecules of alkene oxides diesters with varying HLB values and molecular weights (ED1, ED2, ED3, PD1, PD2 and PD3) were synthesized, elsewhere (Alsabagh et al., 2016). The demulsification efficiency was evaluated at field and reservoir conditions. At field conditions (60 °C and 1 atm) the data revealed that the maximum demulsification efficiency was obtained by ED3 and PD3 at 60 °C, 600 ppm after 55 and 40 min, respectively. At reservoir conditions (85 °C and 5000 psi), the PD3 and ED3 showed also the maximum demulsification efficiency was 76% and 70%, respectively, in spite of the 2% from the blank emulsion (12% BS&W) separated after 7 days. The interfacial tension (IFT) at the crude oil/water interface was measured for PD3 and ED3. From the results, it was found that the values of IFT were 0.7 and 0.8 mN m−1 respectively. The rheological behavior of the same demulsifiers was investigated. The results showed that the demulsifiers PD3 and ED3 enhance the dynamic viscosities (3.9 and 3.8 mPa s, respectively) and the (τB) yield values were 0.77 and 1.23 Pa s, respectively at temperature 85 °C, whereas, they were 3.95 mPa s and 1.5 Pa s for the blank emulsion sample.